2021
DOI: 10.2147/ijgm.s331772
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Electrical Impedance Tomography During the Ventilator Weaning Process

Abstract: Background: This study proposes the investigation of electrical impedance tomography (EIT) as a useful predictor for ventilator weaning. Methods: The study design was a nested case-control study and patients who were admitted to the intensive care unit and underwent their first tracheal intubation were enrolled. Those who successfully completed ventilator weaning and extubation after the first spontaneous breathing trial (SBT) were included in the weaning success group, while those who did not pass the SBT or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Moon et al recently found that GI was significantly greater in patients failing a T-piece SBT, in a population of 40 patients either with ( n =16) or without ( n =24) diaphragm dysfunction [ 83 ]. In keeping with these previous results [ 81 83 ], in 53 patients mechanically ventilated for more than 72 h and undergoing their first T-piece SBT, Wang et al further confirmed that GI prior to SBT helps to predict SBT outcome [ 84 ].…”
Section: Introductionsupporting
confidence: 69%
“…Moon et al recently found that GI was significantly greater in patients failing a T-piece SBT, in a population of 40 patients either with ( n =16) or without ( n =24) diaphragm dysfunction [ 83 ]. In keeping with these previous results [ 81 83 ], in 53 patients mechanically ventilated for more than 72 h and undergoing their first T-piece SBT, Wang et al further confirmed that GI prior to SBT helps to predict SBT outcome [ 84 ].…”
Section: Introductionsupporting
confidence: 69%
“…It was shown that in patients with an initial GI > 41.5, an SBT was more likely to fail, with a sensitivity of 87.5% and a specificity of 60.9%, which suggested that EIT could predict the failure of weaning. Wang et al found that the EIT may be a useful adjunctive tool for evaluating ventilator weaning using pre-SBT GI and SBT ROI 2 (four ROIs were divided from the ventral to dorsal, with ROI 2 being the second region) as predictors ( Wang et al, 2021 ). In addition to weaning failure due to pulmonary system dysfunction, phrenic nerve injury can also lead to atelectasis, difficult weaning, and prolonged ventilation in lung transplantation ( Hernández-Hernández et al, 2022 ).…”
Section: The Future Of Eit In Lung Transplantationmentioning
confidence: 99%